EFFECT OF SERVICES, PRODUCTS AND PRICES ON PURCHASE DECISIONS AT PT. SURYA MEDIKA UTAMA SURABAYA - Aliyu Rofika Romadhona; I Gede Arimbawa (NAROTAMA UNIVERSITY, Indonesia, 2018)
The problems discussed in this study are: whether services, products, and prices have a significant effect on purchasing decisions simultaneously and whether services, products, and prices have a significant effect on purchasing decisions partially. The purpose of this study is to analyze and analyze whether services, products, and prices simultaneous influence on purchasing decisions and to analyze tests and analyze whether services, products, and prices partially influence purchasing decisions. The object of this research was carried out on customers from PT. Surya Medika Utama Surabaya.